2015
DOI: 10.7860/jcdr/2015/13588.5833
|View full text |Cite
|
Sign up to set email alerts
|

An Early and Rare Second Malignancy in A Treated Glioblastoma Multiforme: Is It Radiation or Temozolomide?

Abstract: Glioblastoma Multiforme (GBM) is a high-grade brain tumour with the most dismal prognosis. There are very few reports on second malignancies occurring in GBM patients, as the survival has been short. Second malignancies have been reported after treatment of malignancies with radiation therapy and chemotherapy especially after 5 to 10 y of treatment. Here in, we present a very unique case where a patient succumbed to sinonasal carcinoma occurring one and half years after treatment of GBM. A 17-year-old boy was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Nine studies (10 patient cases) were immediately included in the review. [24][25][26][27][28][29][30][31][32] A metaanalysis was identified 33 which included two relevant case reports from studies not identified in the initial search; these two case reports were also included. 34,35 One study which described two additional relevant case reports was also identified by screening the references of included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies (10 patient cases) were immediately included in the review. [24][25][26][27][28][29][30][31][32] A metaanalysis was identified 33 which included two relevant case reports from studies not identified in the initial search; these two case reports were also included. 34,35 One study which described two additional relevant case reports was also identified by screening the references of included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Glioblastoma multiforme (GBM) is the most common and aggressive primary brain tumor among adults, with an average survival of approximately 15 months. , The standard protocol available for the treatment of GBM consists of maximal safe surgical resection, followed by radiotherapy, plus concomitant and adjuvant chemotherapy with the alkylating agent temozolamide (TMZ). , However, at least 50% of TMZ-treated patients do not respond to this agent. Moreover, hematological malignancies such as acute lymphoblastic leukemia, acute myeloid leukemia and myelodysplastic syndrome have been reported to occur after treatment with TMZ. …”
Section: Results and Discussionmentioning
confidence: 99%
“…Importantly, hTP is overexpressed in GBM, whereas undetectable or trace levels are found in the normal human brain. The occurrences of microvascular proliferation, invasion, and resistance to apoptosis are hallmarks of glioblastoma. , Antiangiogenic therapy is considered an important target for GBM treatment, and several clinical trials enrolling antiangiogenic agents are in progress. , The novel strategies for GBM treatment are focused on the modulation of vessel permeability, hypoxia, and tumor-induced edema. ,, …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Goyal et al 10 reported a case of a sinonasal carcinoma occurring 1.5 years post-GBM radiotherapy treatment and outside the radiation field, however, in that case, due to the short interval time, radiation therapy was unlikely to be the cause of the second malignancy and therefore the malignancy did not meet Cahan's criteria. The case we have described here presents a rare event whereby the criteria for a radiation-induced tumour were met, due to the patient surviving significantly longer than would otherwise be expected following surgical treatment of GBM.…”
Section: Discussionmentioning
confidence: 99%